Infiltration rates, surface runoff, and soil loss as influenced by grazing pressure in the Ethiopian highlands - Mwendera, E.J.; Mohamed-Saleem, M.A. (Wiley, 1997)
The effect of grazing pressure on infiltration, runoff, and soil loss was studied on a natural pasture during the rainy season of 1995 in the Ethiopian highlands. The study was conducted at two sites with 0-4 percent and 4-8 percent slopes at the International Livestock Research Institute (ILRI) Debre Zeit research station, 50 km south of Addis Ababa. The grazing regimes were: light grazing stocked at 0.6 animal-unit-months (AUM)/ha; moderate grazing stocked at 1.8 AUM/ha; heavy grazing stocked at 3.0 AUM/ha; very heavy grazing stocked at 4.2 AUM/ha; very heavy grazing on ploughed soil stocked at 4.2 AUM/ha; and a control with no grazing. Heavy to very heavy grazing pressure significantly reduced biomass amounts, ground vegetative cover, increased surface runoff and soil loss, and reduced infiltrability of the soil. Reduction in infiltration rates was greater on soils which had been ploughed and exposed to very heavy trampling. It was observed that, for the same percent vegetative cover, more soil loss occurred from plots on steep than gentle slopes, and that gentle slopes could withstand more grazing pressure without seriously affecting the ground biomass regeneration compared to steeper slopes. Thus, there is a need for developing `slope-specific' grazing management schedules particularly in the highland ecozones rather than making blanket recommendations for all slopes. More research is needed to quantify annual biophysical changes in order to assess cumulative long-term effects of grazing and trampling on vegetation, soil, and hydrology of grazing lands. Modelling such effects is essential for land use planning in this fragile highland environment.